PEMBIASAAN PERILAKU ISLAM SEBAGAI BUDAYA SEKOLAH DI KELAS X SMK NEGERI 4 MAKASSAR - Muh. Husain; Ahmad Hakim; Nukman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aimed to analyse the implementation process of students'behavioural activities, identify the developed values of Islamic behaviours, andevaluate the effectiveness of the Qur’anic recitation (Khataman) program inshaping student behaviours at SMK Negeri 4 Makassar. These activities wereconducted during school days as part of a strategy to cultivate habitual Islamicbehaviours within the school environment. A descriptive qualitative approach wasemployed. Data were collected through observations, in-depth interviews, andquestionnaires administered to students participating in the Khataman program aswell as to program mentors. Inductive analysis was used to interpret the meaningsand impacts of these activities on behaviours formation. The findings of the studywere: 1) the planning of Islamic behaviours habituation begins with the formulationof Islamic-based vision and mission statements, followed by the development ofworship behaviours standards (ubudiyah). As part of this process, Islamiceducation teachers promote religious behaviours and plan spiritual activities withinthe school, serving as a means to foster a religious atmosphere and enhanceIslamic education learning, 2) Islamic behaviours was instilled through a series ofregular activities—daily, weekly, monthly, and annual, 3) the habituation of Islamicbehaviours contributed to the formation of a Muslim personality in students. AQur’anic character can be developed through consistent religious practicesimplemented within the school. In conclusion, the habituation of Islamicbehaviours is essential in daily life, particularly in the school environment, as italigns with and reinforces Islamic values.